Cyber Education and the Emerging Profession of Cybersecurity. Issue 5 (1st November 2016) - Shoemaker, Dan; Kohnke, Anne
Abstract: Education shapes behavior and, for that reason, a comprehensive study of an important emerging field like cybersecurity can be a powerful agent for societal change. However, there are a number of systemic and cultural challenges that have to be overcome before education can become a practical solution. If we distribute the teaching of cybersecurity in diverse places on campus, students are not going to get a coherent understanding, let alone practice overall cybersecurity effectively. A broad-scale educational understanding of the field must be developed based on a comprehensive definition of legitimate threats. Technological solutions solve specific problems, consequently we have been very successful in situations involving well-defined and established physical challenges. What we have not dealt with is the human behavior and creative thinking that characterizes the exploits of the hacker community, and until the solution incorporates actions that recognize and address every reasonable form of attack, we will never be secure.